SiGe Bandgap Tuning for High Speed Eam. (27th April 2017) - Mastronardi, Lorenzo; Banakar, Mehdi; Khokhar, Ali Z.; Domínguez Bucio, Thalía; Littlejohns, Callum G; Bernier, Nicolas; Robin, Eric; Rouviere, Jean-Ruc; Dansas, Hugo; Gambacorti, Narciso; Mashanovich, Goran Z.; Gardes, Frederic Y.
Abstract : We report bandgap engineering of Ge rich SiGe rib waveguides between 1550 nm and 1580 nm through an annealing process. The insertion loss of the material (transmission spectrum) is analysed between 1520 nm and 1600 nm. The experimental data are elaborated by implementing the Tauc Method analysis, and the material bandgap estimation is calculated. A maximum blue shift of 38 nm, with an overall reduction of Si content, suggests that the diffusion of Si in the Ge seed layer during anneal improves the homogeneity of the growth layer. The proposed technique provides a path for tailoring the operational wavelength of devices such as electro-absorption modulators, realized on an SOI platform.